2019
DOI: 10.3390/ijms20102473
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 Contributes to Distant Metastasis and Poor Prognosis by Promoting Angiogenesis in Oral Squamous Cell Carcinoma

Abstract: The highly malignant phenotype of oral squamous cell carcinoma (OSCC), including the presence of nodal and distant metastasis, reduces patient survival. High-mobility group A protein 2 (HMGA2) is a non-histone chromatin factor that is involved in advanced malignant phenotypes and poor prognosis in several human cancers. However, its biological role in OSCC remains to be elucidated. The purpose of this study was to determine the clinical significance and role of HMGA2 in the malignant potential of OSCC. We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 42 publications
(59 reference statements)
2
32
0
Order By: Relevance
“…More recently, HMGA1 was shown to interact with the FOXM1 transcription factor for VEGFA promoter binding, inducing tumor angiogenesis in HUVEC cells and in zebrafish xenografts [261]. Similarly, there are also evidences of HMGA2 being involved in the regulation of pro-angiogenic genes like VEGFA, VEGFC, and FGF-2 [262] and in the angiogenesis occurring in diabetic retinopathy [263] ( Figure 3F).…”
Section: Other Developmental Effects Of Hmgamentioning
confidence: 86%
“…More recently, HMGA1 was shown to interact with the FOXM1 transcription factor for VEGFA promoter binding, inducing tumor angiogenesis in HUVEC cells and in zebrafish xenografts [261]. Similarly, there are also evidences of HMGA2 being involved in the regulation of pro-angiogenic genes like VEGFA, VEGFC, and FGF-2 [262] and in the angiogenesis occurring in diabetic retinopathy [263] ( Figure 3F).…”
Section: Other Developmental Effects Of Hmgamentioning
confidence: 86%
“…It was shown that metformin decreases angiogenesis and tumor growth by reducing HMGA2 levels in cervical cancer cells through regulation of miR-142-3p . Metformin was suggested to prevent miR-142 sponging to allow targeting of HMGA2 [ 145 ]. It was further reported that miR-1249 suppresses colorectal cancer (CRC) angiogenesis by targeting both VEGFA and HMGA2 through the AKT/mTOR signaling pathway [ 146 ].…”
Section: Hmga2 Promotes Angiogenesis During Cancer Developmentmentioning
confidence: 99%
“…Similar findings to our study were reported by Sakata et al who observed a strong correlation of HMGA2 expression with distant metastasis and poor prognosis. However, they explored HMGA2 expression via immunostaining in 110 OSCC patients (Sakata et al, 2019).…”
Section: Discussionmentioning
confidence: 99%